Chemical Composition of the Essential Oil from Nepeta macrosiphon Boiss. Growing Wild in Iran by Different Extraction Methods and Studies on the Quantitative Relationship Between the Retention Indices of Essential Oils and their Molecular Structures - Aberoomand Azar, Parviz; Zare, Karim; Saber-Tehrani, Mohammad; Jafari Kokhedan, Azizolah; Vafaei, Azam; Nekoei, Mehdi; Larijani, Kambiz (Asian Journal of Chemistry, 2013)
Hydrodistillation, solvent free microwave extraction and solid phase microextraction methods has been applied to extraction of essential oil from Nepeta macrosiphon growing in Iran. Spathulenol (28.8, 32.28 and 7.68) and b-caryophyllene (9.6,5.83 and 15.19) were the main compounds in the essential oil, respectively. High amount of sesquiterpenes and low quantity of hydrocarbon monoterpenes were identified in the essential oils. Then a simple, strong, descriptive and interpretable model, based on a quantitative structure-retention relationship is developed using stepwise multiple linear regression (SW-MLR) approach for prediction of the retention index (RI) of Nepeta macrosiphon essential oil. A model with low prediction error (2.071 %) and good coefficient of determination (0.982) was obtained. This model was used for the prediction of the RI values of some essential oil components which were not used in the modeling procedure.